Low compliance with dietary recommendations among Iranian women: a dietary pattern survey - Hashemi, Seyedeh Zeinab; Vahidinia, Aliasghar; Hazavehei, Seyed Mohammad Mehdi; Karimi-Shahanjarini, Akram; Poorolajal, Jalal; Erfani, Hossein; Shahabadi, Sara (Progress in Nutrition, 2019)
Background: Identification of dietary behaviors of women is one of the most substantial concerns in order to improve family nutritional behaviors. Due to primary influence of a mother in family food choices, this study aimed to investigate the nutrition behaviors according the dietary recommendations of the food guide pyramid among women living in Hamadan, Iran. Methods: This cross-sectional study on the mothers’ nutritional behaviors was carried out from May to June 2014. In this study 1084 mothers aged 23-49 years of elementary school children were selected to participate in this study using stratified cluster random sampling method. Data were collected using the validated Iranian 168-item semi-quantitative Food Frequency Questionnaire (FFQ). The dietary assessment was based on the five major groups of food guide pyramid. Stata version 11 was used for data analysis. Results: Our results revealed that 72.7%, 67.8%, 52.9% and 55.5% of subjects consumed less dairy products, vegetables, fruits and meat/alternatives, respectively, as compared to the food pyramid recommendations. However, bread and grains intake in 40.4% of subjects were more than recommendations. Consumption of pizza and processed meats in about 40% of subjects were monthly and in about 20% were weekly. There was a significant relationship between the household income and education level with the intake of five major groups of food guide pyramid. Conclusion: There were unhealthy dietary habits and low compliance with dietary recommendations among majority of women. Our findings may be considered in policy-making process involving development of health promotion interventions that are appropriately tailored according to different incomes and educational levels to improve family healthy eating habits.